TEMOZOLOMIDE THERAPY IN RECURRENT METASTATIC PHEOCHROMOCYTOMA: A CASE-BASED REVIEW - Nordin, Hidayatil Alimi Bin Keya; Voon, Tong Chin; Hussein, Zanariah Binti (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Metastatic pheochromocytoma is rare and the management is complex, requiring multifaceted, multidisciplinary management. Primarily palliative, treatment focuses on tumor control, symptom management, and quality of life. While historically associated with a poor prognosis, improved diagnosis and management, including surgery, chemotherapy and targeted therapies, are extending survival for some patients. CASE A 52-year-old female was initially diagnosed in 2013 with non-functioning pheochromocytoma with liver, spleen, and pancreatic tail metastases. She underwent left adrenalectomy, splenectomy, distal pancreatectomy, and local resection of metastatic liver lesions, followed by trans-arterial chemoembolization of liver metastases. Subsequent follow-up imaging revealed recurrent disease, necessitating further surgical intervention. This included left hemihepatectomy, left nephrectomy, segmental resection of the colon and splenic flexure and excision of a posterior abdominal tumor. Due to the extensive nature of her disease progression, the patient received 4 cycles of peptide receptor radionuclide therapy (PRRT) as well as palliative radiotherapy to left thoracoabdominal mass and T9 till L1 vertebrae. Despite undergoing PRRT, the disease continued to progress. A multidisciplinary team discussion led to the initiation of temozolomide treatment in March 2023. The patient has received 22 cycles of temozolomide from 2023 to date, with recent follow-up imaging demonstrating partial response to the treatment. CONCLUSION This case report illustrates therapeutic efficacy of temozolomide in metastatic pheochromocytoma. In recent years, temozolomide has shown good outcomes in some metastatic pheochromocytoma patients, especially those with SDHB germline mutation. Temozolomide treatment has been generally considered to have a low toxicity profile, however few studies have noted the development of severe myelosuppression. While the current evidence base is still developing and primarily relies on retrospective data and case reports, ongoing clinical trials are anticipated to yield more definitive conclusions regarding its efficacy and optimal clinical application in metastatic pheochromocytoma.